Menopausal Symptoms and Sleep Quality in Women Aged 40–65 Years - Song, Zicheng; Jiang, Rongzhen; Li, Changbin; Jin, Feng; Tao, Minfang (BioMed research international, 2022)
The study examined the relationship between menopausal symptoms and sleep disturbances and the related influencing factors. Methods. We recruited women aged 40-65 years who attended the menopause clinic at Shanghai Jiao Tong University’s Sixth People’s Hospital from February 2011 to November 2019. The Menopause Rating Scale (MRS) was used to collect women’s menopausal symptoms, and the Pittsburgh Sleep Quality Index (PSQI) was used to evaluate the subjects’ sleep condition. We used logistic regression models to identify the relationship between menopausal symptoms and sleep quality. Results. A total of 1341 participants were recruited in this study. The most frequent three symptoms assessed by MRS were fatigue (72.9%), sleep disturbance (67%), and hot flashes with night sweats (65%). Participants’ age was significantly associated with the severity of menopausal syndrome (P<0.01). According to the PSQI sleep evaluation, 66.9 percent of participants had sleep disturbances (PSQI>5). Logistic regression analysis revealed that women with mild, moderate, or severe menopausal syndrome had a 3-, 7-, and 17-fold increased chance of having sleep disturbances compared to women without menopausal syndrome. Conclusion. Women aged 40–65 years were found to have a significantly higher risk of menopausal syndrome and sleep disturbances.